SesA, sesB, sesC, sesD, sesE, sesG, sesH, and embp genes are genetic markers that differentiate commensal isolates of Staphylococcus epidermidis from isolates that cause prosthetic joint infection. Issue 6 (3rd June 2019) - Ortega-Peña, Silvestre; Vargas-Mendoza, Carlos F.; Franco-Cendejas, Rafael; Aquino-Andrade, Alejandra; Vazquez-Rosas, Guillermo J.; Betanzos-Cabrera, Gabriel; Guerrero-Barajas, Claudia; Jan-Roblero, Janet; Rodríguez-Martínez, Sandra; Cancino-Diaz, Mario E.; Cancino Diaz, Juan C.
Abstract: Objectives: Staphylococcus epidermidis can cause prosthetic joint infections. Strategies to differentiate between healthy skin and prosthetic joint infections isolates are relatively ineffective, which makes necessary to search for new differential biomarkers. Staphylococcus epidermidis has eleven surface proteins, denoted as Ses proteins. In this work, ses genes are used as biomarkers to differentiate between prosthetic joint infections and healthy skin isolates. Methods: All prosthetic joint infections ( n  = 51) and healthy skin ( n  = 51) isolates were genotyped by pulsed-field gel electrophoresis. icaA, embp, sesA-I, and sdr F genes were determined by PCR. The phenotypic data included biofilm production and antibiotic resistance. Results: 10 pulsed-field gel electrophoresis profiles were identified: four profiles were exclusive of prosthetic joint infections isolates, three profiles presented a higher proportion in prosthetic joint infections isolates and three profiles presented a higher proportion in healthy skin isolates. sesA, sesB, sesC, sesD, sesE, sesG, and sesH genes were more prevalent in healthy skin isolates than in prosthetic joint infections isolates ( p  < .05). Prosthetic joint infections isolates were more resistant to oxacillin (78%), ciprofloxacin (60%), levofloxacin (60%), and moxifloxacin (57%). The principal coordinate analysis and a discriminant analysis found that prosthetic joint infections isolates had as discriminant biomarker the biofilm formation, the icaA gene, oxacillin, ciprofloxacin, levofloxacin, moxifloxacin, and gentamicin resistance. In contrast, the healthy skin isolates had as discriminant biomarkers the embp, sesA, sesB, sesC, sesD, sesE, sesG, and sesH genes. Conclusions: These data suggest that ses genes can be considered biomarkers to differentiate between S. epidermidis commensal and prosthetic joint infections clinical.